Sisters of Fortune : a novel - Chehebar, Esther Levy (Random House, 2025)
"The Cohen sisters are at a crossroads. Nina, the eldest, is disillusioned with the tight-knight community she and her sisters were raised in. Fortune, the middle sister, is the center of attention as her wedding approaches, bringing with it pressures and hopes for the future. Lucy, the youngest, is a senior at her yeshiva high school, and recently started sneaking around with a mysterious older bachelor. As Fortune gets closer and closer to standing below the chuppah, the three sisters find themselves in a tug of war between tradition and modernity, balancing what their community wants against what they want for themselves. Overshadowing all of this are Sally, their overprotective mother, and Sitto, their charismatic grandmother who fled Syria in 1992, both of whom are as concerned about what everyone is eating and how good the food tastes, as they are about marital bliss. Sisters of Fortune offers a unique perspective into what it's like to be a young woman coming of age in a cloistered, tightly bound community, while still asking universal questions: What do we dream for ourselves? What do we dream for our families? And, above all, what are we going to eat for dinner?"--